2000
DOI: 10.1142/s0192415x00000155
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Toxicology ofAcacia nilotica

Abstract: The potential toxicity of Acacia nilotica was investigated in rats maintained on 2% and 8% acacia diet for 2 and 4 weeks. A significant reduction in body weight in all acacia-fed groups and a significant decrease in the levels of hemoglobin, serum total protein and total cholesterol in animals fed 8% acacia diet for up to 4 weeks were observed. These effects were, however, reversed one week after treatment termination. No significant changes in serum parameters of hepatic and renal functions, fasting glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The loss of body weight can, often, be a sensitive indicator of toxicity after exposure to toxic substances [33,34]. Although a decrease in body weight was reported in rats fed with 2% and 8% Acacia in the diet for 2 and 4 weeks, the condition was reversed in a few days after termination of the treatment without any mortality [35]. In the present study, maximum gain in body weight was observed in group 3 administered with a dose of 500 mg/kg body weight of A. nilotica (L.) leaf extract (ethyl gallate equivalent of 10 mg/kg) and in group 6 administered with 5 mg/kg body weight of ethyl gallate.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of body weight can, often, be a sensitive indicator of toxicity after exposure to toxic substances [33,34]. Although a decrease in body weight was reported in rats fed with 2% and 8% Acacia in the diet for 2 and 4 weeks, the condition was reversed in a few days after termination of the treatment without any mortality [35]. In the present study, maximum gain in body weight was observed in group 3 administered with a dose of 500 mg/kg body weight of A. nilotica (L.) leaf extract (ethyl gallate equivalent of 10 mg/kg) and in group 6 administered with 5 mg/kg body weight of ethyl gallate.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that in rats that were fed an 8% A. nilotica diet for up to 4 weeks their body weights were significantly reduced and serum cholesterol and serum total protein significantly decreased. Symptoms reversed 1 week after treatment termination, leading the authors to conclude that A. nilotica had a high toxicity potential [27], but this toxic effect was not irreversible. These findings illustrate that in vitro test results can be extrapolated directly to in vivo effects.…”
Section: Discussionmentioning
confidence: 99%
“…This plant is also known to have anti-inflammatory, anti-oxidant, anti-diarrheal, anti-hypertensive and anti-spasmodic, anti-bacterial, anti-helminthic, anti-platelet aggregatory, and anti-cancer activities [50]. Toxicological studies on A. nicolita showed that it has a low toxicity potential [55]. However it is also reported that repeated administration of doses higher than 250 mg/kg body weight for 28 days caused hepatotoxicity in rats [56].…”
Section: Acacia Nicolita Var Adansonaii (Guill and Perr) Brenanmentioning
confidence: 99%